RISK AND RESPONSIBILITY AT THE FRONTIER OF AI: A THEMATIC ANALYSIS OF DEEP LEARNING PIONEERS’ PERSPECTIVES ON ARTIFICIAL INTELLIGENCE THREATS AND GOVERNANCE - Bojić, Ljubiša (Serbian political thought, 2025)
As artificial intelligence (AI) reshapes global societies, understanding its associated risks and governance imperatives is of urgent social importance. This study fills a critical gap by systematically analyzing extended interviews with Geoffrey Hinton, Yoshua Bengio, and Yann LeCun—the chief architects of deep learning—to elucidate their firsthand perspectives on AI’s existential, ethical, social, and governance challenges. Employing qualitative thematic analysis across six longitudinal interview transcripts, the research identifies both convergences and divergences: Hinton and Bengio strongly emphasize existential threats, superintelligence hazards, AI weapons risks and the need for robust global regulation, while LeCun expresses technological optimism and favors decentralized, open development. All acknowledge economic disruption, misuse potential, and fractures in democratic discourse. The study’s findings reveal that expert opinion on AI risk is far from monolithic and highlights actionable, innovative governance proposals—from regulated compute access to “diversity engines” in social media feeds. Implications include the necessity for adaptive, internationally coordinated AI governance and greater professional accountability among developers. Limitations include a focus on elite, Anglophone experts and inherent subjectivity in qualitative coding. Future research should expand to multi-stakeholder and cross-national perspectives, and test proposed regulatory frameworks in real-world contexts, addressing the ongoing evolution of risk as AI permeates new domains.
Keywords: artificial intelligence risk; deep learning pioneers; AI governance; existential threats; thematic analysis